CEO compensation: US college student and adult perceptions - Clarissa R. Steele; Sarah Holtzen (Organization Management Journal (OMJ), 2024)
Purpose - This study aims to understand differences in perceptions of CEO compensation between working adults and business students in the USA before and after reading CEO pay information. Design/methodology/approach - Participants completed a survey about their perceptions of chief executive officer (CEO) compensation before and after reading CEO compensation information that included the median CEO-to-employee ratio and salary in 2021. Findings - Working adults and business students had similar levels of concern about CEO compensation. Participants were more concerned with CEO compensation after reading information about CEO pay but also believed CEO pay was more justified, contrary to equity theory (Adams, 1965). Among the student and adult samples, women and noninvestors were more likely to have concerns about CEO compensation than other participants. Practical implications - Individuals may not understand the components of CEO compensation, and the size of CEO salaries may be difficult to comprehend. Educators and the media should consider presenting CEO compensation information in a different way, for example, how long it takes a CEO to earn as much as an average employee does annually, for the public to understand how much more CEOs are paid than their employees. Originality/value - Little research exists on CEO compensation understanding and concerns. This research opens the opportunity for future studies on CEO compensation, for example, that consider variables other than CEO pay (e.g. equity and other forms of compensation) and what individuals believe CEOs do that justifies their high compensation.
Keywords: 650; Business students; CEO compensation; Pay perceptions